Determination of FMDV 146S particle concentration by spectrometric method during viral RNA quantification - M. I. Doronin; D. V. Mikhalishin; V. A. Starikov; D. A. Lozovoy; Yu. S. El’kina; A. V. Borisov (Ветеринария сегодня)
During FMD vaccine production, special attention is paid to the concentration of 146S particles bearing the critical biological features of FMDV and being the main components that have an effect on vaccine immunogenicity. For this reason, each batch of vaccine raw material is tested for 146S component concentration. The paper presents the results of the use of a spectrometric method for whole particle concentration determination during quantification of FMDV RNA extracted after immune capture. It is an inexpensive, easy-to-perform method allowing for determination of FMDV 146S particle concentration in the non-inactivated culture suspension. 146S particle concentration was found to depend on the number of RNA molecules extracted from virions after their strain-specific immune capture and quantitatively detected by the spectrometric method. The presented method allows for determination of 146S component concentration in the non-inactivated vaccine raw material using the proposed linear model. The spectrometric method showed 94.5–99.5% correlation with real time reverse transcription polymerase chain reaction and complement fixation test based on the results of tests of 360 non-inactivated suspensions of FMDV of all types. Tests of the positive control demonstrated 99.0–99.6% compatibility of actual and expected results. FMDV genome and 146S particles were not detected in the negative control, and that was in line with expectations.